Dynamic Hip Screw Treatment for Intertrochanteric Fractures in the Elderly: A Summary of Results - Syed Usman Shah, Baber Shahzad Sadiq, Muhammad Zeeshan Iqbal, Muhammad Ali Usman, Syed Maaz Shah, Muhammad Younas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective was to find out how well the Dynamic Hip Screw (DHS) worked after treating intertrochanteric fractures in older patients. Study Design: A descriptive study Place of study & Duration: Ayub Teaching Hospital Abbottabad and Abbottabad International Medical institute Abbottabad. May 2022 to April 2023 Methods: Total 190 patients of both genders were presented in this study. All senior patients who matched the inclusion criteria and had stable intertrochanteric fractures (Evans type IA and Type IB) were evaluated for functional outcome using the Harris Hip Score (HHS). Depending on the HHS score, the results were categorized as exceptional (90 to 100), good (80 to 90), fair (70 to 80), or bad (<70) at 6 months. Results: We found excellent outcomes in 100 (52.6%) cases, good in 57 (30%) cases, 24 (12.2%) found fair and poor outcomes in 9(4.7%) cases. Conclusion: The majority of our elderly patients who underwent Dynamic Hip Screw (DHS) treatment for stable intertrochanteric fractures had excellent and good functional outcomes. When treating stable intertrochanteric fractures in older patients, DHS is the implant of choice. Keywords: Dynamic Hip Screw (DHS), Outcomes, Elder patients.